Pekerjaan dan Analisis Pekerjaan - Nashrullah; Jafar, Jabir M; Parmitasari, Rika Dwi Ayu; Syariati, Alim (Ikatan Dai Indonesia, 2025)
Job analysis is a systematic process aimed at identifying and defining the tasks, responsibilities, and skills required for each position within an organization. This process provides a comprehensive understanding of the roles and qualifications necessary to ensure the alignment of employees' competencies with organizational needs. By offering a detailed insight into the expectations and requirements of various positions, job analysis plays a crucial role in supporting key aspects of human resource management, such as recruitment, employee training and development, performance evaluation, and compensation structuring. his study explores both traditional and modern approaches to job analysis. Traditional methods primarily focus on technical tasks and specific job duties, reflecting a more static perspective of organizational roles. In contrast, modern approaches emphasize adaptability, behavioral competencies, and the alignment of individual values with organizational culture. These methods acknowledge the dynamic nature of today's work environment, where soft skills such as teamwork, problem-solving, and cultural fit are increasingly important. Drawing from an extensive literature review, this research underlines the need to integrate traditional and modern perspectives to create a more effective and holistic job analysis framework. Such an integrated approach ensures that job analysis not only addresses technical requirements but also incorporates behavioral and cultural aspects, enabling organizations to navigate rapidly changing business environments more effectively. Furthermore, it facilitates the development of a more engaged, productive, and adaptive workforce, positioning organizations to achieve sustainable competitive advantages. The findings of this study highlight the critical role of job analysis as a strategic tool for workforce planning and management. By adopting a holistic approach that combines technical precision with adaptability and cultural fit, organizations can optimize their human resources, foster employee satisfaction, and maintain a resilient and competitive workforce.